TEACHING THE USE OF THESAURUSES TO ENGLISH AS A FOREIGN LANGUAGE LEARNERS: PEDAGOGICAL APPROACHES AND LEXICAL DEVELOPMENT (Scientific journal of the Fergana State University, 2026)
The integration of thesaurus instruction into English as a Foreign Language (EFL) curricula represents a critical yet underutilized pedagogical strategy for enhancing lexical competence and promoting vocabulary depth among non-native English speakers. This research investigates the effectiveness of explicit thesaurus training on EFL learners' vocabulary acquisition, synonym recognition, and contextual word selection abilities.